Radioactive emissions and radiation exposures resulting from nuclear power production - Beninson, Dan Jacobo (Comisión Nacional de Energía Atómica; Argentina, 1985)
Fil: Beninson, Dan Jacobo Comisión Nacional de Energía Atómica; Argentina